Enhancing solar power harvesting with pinnacle multipoint optimization: a novel technique for maximum power point tracking - Youssef Mhanni; Youssef Lagmich (Frontiers in Energy Research)
This study introduces a new technique called Pinnacle Multipoint Optimization (PMO) for Maximum Power Point Tracking (MPPT). The approach is specifically developed to improve the performance of photovoltaic (PV) systems in both regular and partially shaded settings. The PMO algorithm adaptively modifies three crucial tracking points to effectively traverse the power-voltage (P-V) curve, guaranteeing precise monitoring (GMPP). The PMO algorithm has been proven to surpass the classic Perturb and Observe (P&O) approach regarding efficiency, tracking speed, and resilience through comprehensive simulations conducted under diverse irradiation settings. More precisely, when there is partial shadowing, the PMO approach demonstrates significant enhancements compared to the P&O method, which only achieves an average efficiency of 54.71%. The PMO algorithm is proficient in optimizing energy output and minimizing power dissipation in photovoltaic systems.